PERAN CITRA BAZNAS TERHADAP PENINGKATAN MINAT MUZAKKI DALAM PENYALURAN ZAKAT PADA BADAN AMIL ZAKAT NASIONAL KOTA BANDUNG - Rivaldianda Putra, Dwiara; Nurnaningsih, Rita; Ma’mun, Saepul (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2025)
An individual's interest in distributing zakat is influenced by the image, belief, belief, and knowledge about the amil zakat institution. This study aims to analyze the influence of the image of the National Amil Zakat Agency (BAZNAS) on the interest of muzakki in distributing zakat in the city of Bandung. The research method used was quantitative with a population of 10,730 muzakki and a purposive sample of 100 respondents. Data was obtained through a questionnaire that measured the variables of BAZNAS image (X) and muzakki interest (Y). The results of the descriptive analysis showed that 53.25% of muzakki were in the category of moderate interest in distributing zakat. The correlation test produced a coefficient of 0.604 which showed a strong linear relationship between the image of BAZNAS and the interest of muzakki. The R Square value of 0.365 indicates that the image of BAZNAS contributes 36.5% to the variation in muzakki's interest, while 63.5% is influenced by other factors outside of this study. The regression equation Y = 31.913 + 0.527X confirms that every one-point increase in the BAZNAS image increases the interest of muzakki by 0.527 points. The hypothesis test showed a positive and significant influence of the BAZNAS image on the interest of muzakki with a tcal value of 0.67703 and a p-value of 0.000 < 0.05, so that the hypothesis was accepted. Thus, the image of BAZNAS has proven to play an important role in increasing the interest of muzakki in distributing zakat through official institutions.